PENINGKATAN KESEJAHTERAAN ANAK YATIM MELALUI USAHA AMDK Q-MAS M - Ummu Atika Azizah; Sri Herianingrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The background of this study is the existence of a business in Q-Mas M which was established by the KH. Mas Mansur Orphanage. This phenomenon encourages researchers to raise research that discusses the contribution of Q-Mas M to the KH. Mas Mansyur in improving the welfare of orphans. This study uses a qualitative approach with a case study strategy. Data collection is done through interview techniques with relevant parties and related documents. The validity test of the data carried out in this study is the source triangulation technique. The data analysis technique used in this study is explanatory manufacturing techniques. The results of this study indicate that the business contribution of Q-Mas M in improving the welfare of orphans has not been fully successful. From the five basic needs that must be fulfilled by orphans, only two that succeed, there are the fulfillment of food and residence needs for orphans.Keywords: contribution, Q-Mas M, welfare, orphanage KH. Mas Mansyur Malang